(untitled) (Acta Horti Botanici Bucurestiensis, 2024)
The presence of species Allium inaequale in the flora of Moldova (eastern Romania), has been reported in this paper, based on specimens collected by authors on the field, as well as on specimens stored in public herbaria. The species has been identified in arid grasslands of two nature reserves from the Central Moldavian Plateau (Vaslui County), namely: “Coasta Rupturile” Tanacu and “Movila lui Burcel” Miclești. This is a very rare plant species in Romania, found at the most western limit of its general range, and should be included, as vulnerable, in the Romanian Red List of Vascular Plants. We have also found that the registration of the species A. moschatum in the flora of Moldova was due to misidentification. Based on the current data, A. moschatum, should be replaced in the flora of this historical province by A. inaequale.